Orientação educacional, diálogo e formação : contribuições da hermenêutica filosófica de Hans-Georg Gadamer - Baldasso, Taís (My University, 2026)
This dissertation addresses the relevance of dialogue in Educational Guidance, understanding it as an important element in the formative process of the subjects involved in the school context. The research from which this dissertation originates set out to investigate the implications of the hermeneutic conception of dialogue for the practice of the Educational Guidance professional, here understood from a dialogical perspective, with emphasis on promoting formative experiences that value listening, openness, and the shared construction of meaning. To achieve this objective, the methodological approach adopted was theoretical-conceptual, based on studies and written works by Gadamer (2015, 2011) to understand the conception of hermeneutic dialogue. Grinspun (2011) appears secondarily, as she provides support for the analysis of the concept of Educational Guidance and the role of the educational counselor. In order to articulate both thematic axes within the field of education, the theoretical contributions of Carbonara (2013), Dalbosco (2006), Flickinger (2014), and Hermann (2002) are also mobilized, whose reflections broaden the debate on formation, experience, and language. The main reflections developed throughout the study converge toward the conception of Educational Guidance as a privileged space for dialogical formation, in which the counselor acts not only as a mediator but as a participant in the educational process in its ethical, political, and formative dimensions. Dialogue, understood in its living, experiential, and transformative dimension, is revealed as a practice that fosters more humane educational processes, in which the singularity of subjects is respected, mutual listening is cultivated, and education is configured as a continuous movement of openness, understanding, and formation. Based on the research conducted, Educational Guidance is assumed with emphasis on its formative and dialogical character, committed to the construction of meaning in the encounter with the other, grounded in philosophical hermeneutics. [resumo fornecido pelo autor]
A presente dissertação aborda a relevância do diálogo na Orientação Educacional, compreendendo-o como elemento importante no processo formativo dos sujeitos envolvidos no contexto escolar. A pesquisa, da qual se origina esta dissertação, propôs-se a investigar as implicações da concepção hermenêutica de diálogo para a atuação do profissional de Orientação Educacional, assumida aqui sob uma perspectiva dialógica, com ênfase na promoção de experiências formativas que valorizem a escuta, a abertura e a construção compartilhada de sentidos. Para alcançar tal objetivo, a abordagem metodológica utilizada foi teórico-conceitual, com base em estudos e produções escritas de Gadamer (2015, 2011) para o entendimento da concepção de diálogo hermenêutico. Grinspun (2011) aparece de forma secundária pois oferece subsídio para a análise do conceito de Orientação Educacional e do papel do orientador educacional. A fim de articular ambos os eixos temáticos ao campo da educação, também são mobilizadas as contribuições teóricas de Carbonara (2013), Dalbosco (2006), Flickinger (2014) e Hermann (2002), cujas reflexões ampliam o debate sobre formação, experiência e linguagem. As principais reflexões desenvolvidas ao longo do estudo convergem para a concepção da Orientação Educacional como espaço privilegiado de formação dialógica, no qual o orientador atua não apenas como mediador, mas como partícipe do processo educativo em sua dimensão ética, política e formadora. O diálogo, compreendido em sua dimensão viva, experiencial e transformadora, revela-se como prática que favorece processos educativos mais humanos, nos quais a singularidade dos sujeitos é respeitada, a escuta mútua é cultivada e a educação se configura como um movimento contínuo de abertura, compreensão e formação. A partir da pesquisa desenvolvida, assume-se a Orientação Educacional com ênfase no seu caráter formativo e dialógico, comprometida com a construção de sentido no encontro com o outro, tomando-se por base a hermenêutica filosófica. [resumo fornecido pelo autor]
Keywords: Orientação educacional; Hermenêutica; Diálogo; Gadamer, Hans-Georg, 1900-2002 - Crítica e interpretação; Professores - Formação; Educational counseling; Hermeneutics; Dialogue; Teachers; Training of